Evaluasi Perbandingan Efisiensi Biaya Terhadap Metode Pelaksanaan Pekerjaan Struktur Rumah Lantai 3 Di Kota Depok - Nesya, Badzlina Harvy; Alvanda, Muhammad Reyhan (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Depok City as a city with significant population growth every year requires vertical housing infrastructure to meet the needs of housing. The construction of a 3-storey house requires a strong structure and is in accordance with user safety rules so that it can support vertical and lateral loads and is efficient in terms of work procedures and cost factors. Therefore, the selection of implementation methods for structural work is a crucial thing that needs to be studied in terms of quality factors and costs that will be incurred. This study provides alternative recommendations for selecting implementation methods for 3-storey house structural work items with an evaluation of the methods implemented and the costs incurred. The implementation methods provided include structural work using instant concrete, mini mix concrete, steel structures, and containers. From the results of the evaluation carried out, in terms of the cost of structural work, the recommended implementation method is to use instant concrete with a total cost of Rp157,254,996.90. This method is recommended because the costs incurred are more economical, there is no need for mobilization of heavy equipment such as cranes and truck mixers, and it does not have the potential to interfere with access for residents around the construction site. The implementation methods that are less recommended are using mini mix concrete with a total cost of Rp150,190,417.15, steel structures with a cost of Rp292,455,790.28, and containers with a cost of Rp76,900,000.00 taking into account access to the project location, mobilization of heavy equipment, and the costs incurred.